The Src homology and collagen A (ShcA) adaptor protein may participate in the pathogenesis of membranous lupus nephritis. (November 2018) - Cao, W; Liu, X; Xu, X; Zeng, M; Sun, B; Yu, X; Wang, N; Mao, H; Zhang, B; Yuan, Y; Xing, C
The Src homology and collagen A (ShcA) adaptor protein that binds to tyrosine kinase receptors. ShcA plays a role in insulin signaling, stress resistance and energy metabolism. The 66-kDa Src homology 2 domain-containing protein (p66shc) belongs to the ShcA family and has been associated with reactive oxygen species (ROS); increased ROS is involved in the pathology of lupus nephritis (LN). However, whether ShcA can act as a biomarker for oxidative injury in LN is unknown. This study is aimed to investigate the ShcA expression in kidney tissues from patients presenting with LN and the association between ShcA expression and clinical parameters. Renal biopsy tissues were obtained from 62 LN, 20 primary membranous nephropathy (MN) and 10 other secondary MN patients. ShcA was measured by immunofluorescence. The expression of ShcA in the membranous lupus nephritis (class V) group showed a higher trend but there were no significant differences compared with pure mesangial disease (class II) and proliferative (Class III/IV) lupus nephritis. ShcA deposits were negative in primary and other secondary MN. ShcA might act as a new biomarker and a diagnostic tool to identify membranous lupus nephritis with other MN.